2007
DOI: 10.1089/sur.2006.068
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death after Pancreatic Head Resection: Rupture of Hepatic Artery Caused by Clostridial Infection

Abstract: Close monitoring and early recourse to invasive diagnostic and therapeutic procedures may be advisable in the presence of suspect findings after pancreatic surgery to prevent this fatal complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…51 When C. perfringens affects splanchnic arteries, it may cause massive exsanguination and sudden death. Königsrainer et al 52 described a case of sudden death due to a ruptured hepatic artery caused by C. perfringens infection after pancreatic head resection. If abundant gas production occurs within the arteries of vital organs, it can cause circulatory disturbances and sudden death, as reported in the case of cerebral gas embolism.…”
Section: Discussionmentioning
confidence: 99%
“…51 When C. perfringens affects splanchnic arteries, it may cause massive exsanguination and sudden death. Königsrainer et al 52 described a case of sudden death due to a ruptured hepatic artery caused by C. perfringens infection after pancreatic head resection. If abundant gas production occurs within the arteries of vital organs, it can cause circulatory disturbances and sudden death, as reported in the case of cerebral gas embolism.…”
Section: Discussionmentioning
confidence: 99%
“…Rezvani et al reported on a late liver abscess after Whipple procedure associated with stenting of the bile duct and recently, fatal cases of liver gasgangrene after pancreatic surgery have been described [45][46][47]. A mixed infection with the reported three unusual pathogens has not been described thus far.…”
Section: Discussionmentioning
confidence: 99%